Value Creation and Institutional Dynamics in Dairy Systems in Colombia - Urrego, Jackeline Andrea Macías; Herrera, Jaime Andrés Ararat; Restrepo, Luz Alexandra Montoya (Journal of Cultural Analysis and Social Change, 2026)
Context: The dairy sector contributes 24.3% to Colombia's livestock GDP, with Northern Antioquia serving as the country’s primary specialized dairy basin. This production system characterized by small-scale family producers organized into cooperatives faces critical structural challenges: trade liberalization (due to Free Trade Agreements in 2026), rural labor shortages, and a crisis of generational succession. While quantitative studies have previously characterized its productivity and competitiveness, there is limited research regarding how actors co-create value, and which formal and informal institutional configurations shape their economic practices. Methods: This qualitative study employs a sequential design grounded in two systematic literature reviews. Fifteen theoretical codes were derived across three core constructs: Value Creation, Institutional Framework, and Competitive Advantage. Data collection involved 24 semi-structured interviews with producers (small, medium, and large), processors, and cooperative representatives, complemented by 10 non-participant farm observations. A directed qualitative content analysis was conducted, combining deductive and inductive coding with methodological triangulation to ensure analytical rigor and credibility. Results: The analysis yielded 2,438 codifications. The central finding is the marked predominance of informal institutions over formal ones at a ratio of 2.4:1 (376 vs. 157 codifications), demonstrating that shared values, interpersonal trust, and generational tradition constitute the primary regulatory framework for economic behavior. Ten unanticipated themes emerged, notably: family structure as a source of competitive advantage (347 mentions), time/continuity as a dimension of value (206 mentions), and democratic participation in cooperatives as a mechanism for co-creation (154 mentions). Co-occurrence analysis revealed that cooperatives function as hybrid institutional spaces that bridge the formal-informal divide, mitigating institutional voids through volume aggregation, collective bargaining, and the provision of specialized technical services. Conclusions: This study offers four theoretical contributions: (1) it empirically documents the institutional predominance of the informal in traditional agro-industrial chains, extending institutional theory to the family-based dairy context; (2) it identifies emerging dimensions of value (temporality and ethics) previously overlooked in the literature; (3) it conceptualizes "economies of family scope" as an alternative source of competitive advantage that challenges traditional Porterian assumptions; and (4) it characterizes the cooperative model as an effective mechanism for reducing institutional voids. These findings have significant implications for public policy, suggesting that strategic interventions must align with, rather than oppose, existing informal institutional frameworks.